2010
DOI: 10.1111/j.1472-8206.2009.00791.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatal liver injury associated with clopidogrel

Abstract: Clopidogrel, an adenosine diphosphate receptor blocker, is widely used as an adjunctive antiplatelet therapy in acute coronary syndrome and percutaneous coronary stenting. It appears to be a safe drug with few occurrences of liver side-effects that usually resolved after drug withdrawal. We report a serious liver injury with fatal outcome in a 63-year-old man developed 19 days after starting clopidogrel for percutaneous coronary stenting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…In humans, at least one episode of idiosyncratic hepatotoxicity and progressive liver failure has been attributed to the antiplatelet drug clopidogrel (11). Millions of individuals take drugs that alter 5-HT homeostasis as treatments for depression and other neuropsychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, at least one episode of idiosyncratic hepatotoxicity and progressive liver failure has been attributed to the antiplatelet drug clopidogrel (11). Millions of individuals take drugs that alter 5-HT homeostasis as treatments for depression and other neuropsychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…increased with age [364]. Various side effects have been reported for both clopidogrel (bleeding, liver and bone injury, enhanced lipopolysaccharide-induced inflammation) [365,366] and ticagrelor (bleeding, dyspnoea) [367]. In more recent reports, it was suggested that there may be a role for endogenous adenosine in ticagrelor-induced dyspnoea [368,369].…”
Section: Thrombosismentioning
confidence: 99%
“…39 These include eight men and four women, aged 56–89 years old, that developed liver injury 4 days to 6 months after clopidogrel intake. The pattern of liver injury was mainly mixed hepatocelullar-cholestatic, but hepatocellular liver injury and systemic inflammatory response syndrome with hepatic injury were also observed.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent case of clopidogrel liver injury with liver failure and fatal outcome was published. 3 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation